The Clavicle Continues to Grow during Adolescence and Early Adulthood. Issue 2 (December 2020) - Hughes, Jessica L.; Newton, Peter O.; Bastrom, Tracey; Fabricant, Peter D.; Pennock, Andrew T.
Background: As more adults undergo surgical fixation of clavicle fractures with improved outcomes, interest is renewed in managing clavicle fractures in adolescents. The medial clavicular physis does not fuse until 23 to 25 years of age, but studies report minimal clavicular growth during adolescence—studies that employed cross-sectional methodologies, which cannot not capture growth in patients over time. The assumption that clavicle length at each stage is uniform, as is the final overall length, may not be accurate if the age groups studied comprise various ethnicities, socioeconomic status, or height. Questions/Purposes: We sought to quantify longitudinal clavicular growth on serial radiographs in adolescents and young adults. Our hypothesis was that substantial clavicular growth would be seen beyond the age of 12 years. Methods: We conducted a longitudinal case series of non-syndromic patients in a single orthopedic clinic and analyzed serial radiographic images of the clavicles. For ethical reasons, only patients with non-neuromuscular scoliosis and kyphosis (in whom the existing standard of care includes serial thoracic radiographs) were considered for inclusion. Patients ages 10 to 25 years old were included in the study if three or more serial thoracic radiographs over a minimum 5 years were available that captured the entire length of at least one non-rotated clavicle. Three types of radiographs were included for analysis: digital low-dose-radiation stereoradiographic (EOS Imaging, Paris, France), non-EOS digital, and non-EOS printed. The overall longitudinal growth, yearly growth, and the yearly growth percentage were calculated for each clavicle. Results: Fifty-seven patients (22 male and 35 female) met the inclusion criteria. In male patients, at ages 12 to 15 years, the clavicular growth was 4.9 mm/year, or 4%/year; at ages 16 to 19 years, growth was 3.2 mm/year, or 2.4%/year; and at ages 20 to 25 years, growth was 1.7 mm/year, or 1.1%/year. In female patients, at ages 12 to 15 years, growth was 4.7 mm/year, or 4%/year; at 16 to 19 years, growth was 2.2 mm/year, or 1.7%/year; and at ages 20 to 25 years, growth was 0.2 mm/year or 0.1%/year. We could not detect the age of terminal growth in either sex because growth was ongoing in most patients in the oldest group. Conclusion: We found substantial clavicular growth potential after age 18 years, when growth is thought to be nearly finished, as well as remodeling potential even up to age 25 years. Further research is needed, but our findings suggest that strategies for managing clavicle fracture in adults may not be applied universally to adolescents and young adults.